Complex evaluation of Raman spectra using morphological filtering: Algorithms, software implementation, and experimental verification of baseline correction, peak recognition, and cosmic ray removal in SERS spectra of designer drugs. (19th September 2022) - Pavelka, Vít; Hemzal, Dušan; Hrbáč, Jan
Abstract: We discuss a full‐scale treatment of real‐life Raman spectra with pronounced artifacts via mathematical morphology: Baseline correction, peak recognition, and cosmic ray removal are provided using a single kernel. The suggested treatment is peak‐oriented, and its novelty lies in utilization of contact points between a spectrum and its morphological mapping to provide robust peak recognition via low‐order morphological operators. Reaching a compromise between complicated iterative processing and requiring tedious input from the user, the provided algorithms permit effective unsupervised evaluation of individual spectra as well as Raman maps and time or depth series. The method is demonstrated on SERS identification of selected designer drugs. Abstract : A morphological operators based algorithm for baseline subtraction and peak recognition within Raman spectra is presented and implemented. Based on the two characteristic widths (of peaks and of background structures), the presented two‐pass algorithm is user‐friendly, robust, and computationally effective as demonstrated on processing of the SERS spectra of selected designer drugs. The peak‐oriented output of the algorithm allows for improved database identification of the spectra.